Light controlled resistive switching and photovoltaic effects in ferroelectric 0.5Ba(Zr0.2Ti0.8)O3-0.5(Ba0.7Ca0.3)TiO3 thin films - Silva, J. P. B. (2017)
In this work, the structural and ferroelectric properties of 0.5Ba(Zr0.2Ti0.8)O3-0.5(Ba0.7Ca0.3)TiO3 (0.5BZT-0.5BCT) thin films deposited at different pulse repetition rates were studied. The films deposited at pulse repetition rate of 1 Hz display the optimum values of ferroelectric polarization and dielectric permittivity and are chosen for the investigation of resistive switching and photovoltaic studies. The Pt/0.5BZT-0.5BCT/ITO capacitors show the electroforming free resistive switching (RS) and is explained based on the polarization modulation of the Schottky barrier at the 0.5BZT-0.5BCT/ITO interface. Furthermore, it is shown that the RS ratio and switching voltage can be tuned with white light illumination. The capacitors display photovoltaic effect with the open circuit voltage ≈0.8 V and the short circuit current density ≈72.6 μAcm−2. The photovoltaic efficiency is found to be ≈0.010% and is greater than that of other perovskite ferroelectric thin films. The underlying mechanism for enhanced RS and photovoltaic effects is highlighted.